GAMBARAN STATUS GIZI ANAK SEKOLAH DASAR DAERAH EKS-TRANSMIGRASI DAN PENDUDUK LOKAL DI KECAMATAN PELAWAN KABUPATEN SAROLANGUN PROVINSI JAMBI TAHUN 2012 - Darmawan Siagian; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Nutritional status of school children is determined by balanced food consumption as well as role of parents, and the awareness of the primary school children. The eating habit of the primary school children is influenced by their culture and the condition of their family income. The purpose of this descriptive study with cross-sectional design was to find out the description of the nutritional status of the primary school children of the ex-transmigration area and local people in Pelawan Subdistrict The population of this study was all of the 3,933 primary school children of the ex-transmigration area and local people, and 184 of them were selected to be the samples for this study through purposive sampling technique with proportion estimation formula. The data for this study were obtained through measuring body weight and body height and food-recal and food-frequency based interviews. The result of this study showed that, based on the IMT, by age, most of the nutritional status of the primary school children in the ex-transmigration area and in the local people area was in normal category; but 11.0% of the  primary school children in the ex-transmigration area and 20.4% in the local people area were in thin category, whereas 4.4% of the  primary school children in the ex-transmigration area and 2.2% in the local people area were in overweight category. Based on Body Height, by age, most of the  nutritional status of the primary school children in the ex-transmigration area and  in the local people area were in normal category; but 26.4% of the  primary school children in the ex-transmigration area and 40.9% in the local people area were in short and very short category. Based on the energy level, 75.9% of the primary school children in the ex-transmigration area and 87.1% in the local people area were in inadequate category. Based on the protein consumption level, 65.9% of the  primary school children in the ex-transmigration area and 80.7% in the local people area were in inadequate category. It is suggested that the food consumption, especially for energy and protein consumption be better improved that the nutritional status becomes normal then make an education or counseling about the balanced nutrition in schools and in community, and for the government should pay more attention and make a policy related to the use of agricultural land for food crops as well as the improvement of community’s economy. Keywords: Nutritional Status, Primary School Children, Ex-Transmigration Community, Local People